The future of management education - Fellenz, Martin R.; Brady, Mairead; Hoidn, Sabine (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"To remain relevant, management education must reflect the realities that influence its subject matter, management, while at the same time addressing societal needs and expectations. Faced by powerful drivers of change, many of which are amplified by the immense turbulence that has characterized the time since the outbreak of the global Covid-19 pandemic in early 2020, an assessment of where management education stands and where it is going is timely. This book brings together management education scholars, practitioners, and stakeholders to identify trends and to critically analyse key challenges from their respective perspectives. They consider the requirements for providing relevant management education in the future and explore changes and opportunities around themes such as responsibility, sustainability, innovation, competitive strategy, and technological change. The different perspectives of the authors contribute distinct insights and form a fascinating kaleidoscope of reflections on the presence and predictions and prescriptions for the future of management education. The result is a comprehensive volume that will be essential reading for scholars and administrators committed to the growth and development of management education. It also will be of keen interest to management educators as well as management learners who will shape and be shaped by the management education of the future"--
Keywords: Management -- Study and teaching (Higher); Business education; BUSINESS & ECONOMICS / Education